Pemanfaatan Data Rapor Pendidikan Dalam Perencanaan Berbasis Data Di SDN 03 Setalik: Sebuah Studi Kualitatif - Agus Elpin; Taufan Untung Wibowo Silitonga; Nuri Simarona; Warneri Warneri; Eny Enawaty (Journal on Education, 2024)
This research aims to explore the use of Education Report Card data in the data-based planning process at SDN 03 Setalik. Using qualitative methods, this research explores the experiences and perspectives of school principals, teachers, and other stakeholders on how Education Report Card data is integrated into decision-making and educational planning processes. The research results show that Education Report Card data provides valuable information about student achievement, learning quality, and school climate. However, there are challenges in integrating this data into planning, such as a lack of adequate human resource capacity and policy support. This research highlights the importance of increasing the competence of teachers and school principals, as well as the need for appropriate policy and program support to facilitate the effective use of Education Report Card data in educational planning.